Mesoderm specification and diversification: from single cells to emergent tissues - Ferretti, Elisabetta (Curr Opin Cell Biol, 2019)
The three germ layers — mesoderm, endoderm and ectoderm — constituting the cellular blueprint for the tissues and organs that will form during embryonic development, are specified at gastrulation. Cells of mesodermal origin are the most abundant in the human body, representing a great variety of cell types, including the musculoskeletal system (bone, cartilage and muscle), cardiovascular system (heart, blood and blood vessels), as well as the connective tissues found throughout our bodies. A long-standing question pertains how this panoply of mesodermal cell types arises in a stereotypical fashion in time and space. This review discusses the events associated with mesoderm specification, highlighting the reconstruction of putative developmental trajectories facilitated by recent single-cell ‘omic’ data. We will also discuss the potential of emergent organoid systems to emulate and interrogate the dynamics of lineage specification at cellular resolution.